2017
DOI: 10.1111/trf.14003
|View full text |Cite
|
Sign up to set email alerts
|

Autologous lymphapheresis for the production of chimeric antigen receptor T cells

Abstract: Background Chimeric antigen receptor (CAR) T cells are a promising new immunotherapy. The first step in manufacturing is to collect autologous CD3+ lymphocytes by apheresis. Patients, however, are often leukopenic or have other disease-related complications. We evaluated the feasibility of collecting adequate numbers of CD3+ cells, risk factors for inadequate collections, and the rate of adverse events. Study Design Apheresis lymphocyte collections from patients participating in 3 CAR T cell clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 18 publications
(26 reference statements)
4
117
1
Order By: Relevance
“…The apheresis procedure was safe and well tolerated without any major adverse events, such as bleeding, hypotension, allergic reactions, or symptomatic hypocalcemia. Two prior studies of lymphapheresis for CAR T‐cell production reported a complication rate of 9.8% to 15%, the majority of which are minor and manageable, such as paresthesia, pain, nausea, vomiting, and headache …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apheresis procedure was safe and well tolerated without any major adverse events, such as bleeding, hypotension, allergic reactions, or symptomatic hypocalcemia. Two prior studies of lymphapheresis for CAR T‐cell production reported a complication rate of 9.8% to 15%, the majority of which are minor and manageable, such as paresthesia, pain, nausea, vomiting, and headache …”
Section: Discussionmentioning
confidence: 99%
“…Only 63 collections (88%) were successful in generating sufficient quantities of CAR T cells to meet protocol dose criteria (0.3 to 3.0 × 10 6 transduced CD3+ cells). Lower CD3+ yields were significantly associated with manufacturing failures, which occurred in 5 of 16 patients (31%) with fewer than the target number of CD3+ cells, and 3 of 55 patients (5%) who met the target …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication reported that the minimum T cell number was collected from 97% of apheresis donors and that 77% achieved the target dose. Apheresis complications occurred in 15% of donors, but were easily managed in the clinic [8].…”
Section: Cell Collectionmentioning
confidence: 99%
“…note the prolonged T‐cell lymphopenia associated with bendamustine use . Production of CAR T cells requires an adequate T‐cell harvest, circulating T‐lymphocyte levels <350/μL being strongly associated with CAR T‐cell production failure . Treatments that cause prolonged T‐cell lymphopenia therefore have the potential to preclude subsequent CAR T‐cell therapy.…”
mentioning
confidence: 99%